FRI0473 Patient-physician discordance in global assessment in 401 early axial spondyloarthritis (AXSPA) patients from the desir cohort: what is the effect on outcomes at 3 years?. (15th June 2017) - Desthieux, C; Molto, A; Saraux, A; Fautrel, B; Gossec, L
Abstract : Background: Discordance between patients' and physicians' ratings of disease activity is frequent. We have previously shown this discordance occurs in around 28% of visits in early axSpA though repeated discordance (over several visits) is less frequent (1). Objectives: To assess in patients with early axSpA, the impact at 3 years of repeated discordance on treatment prescription, functional incapacity and remission. Methods: DESIR (Devenir des Spondyloarthropathies Indifférenciées Récentes) is a French, multicenter, longitudinal cohort of patients with early inflammatory back pain suggestive of axSpA (2). Patient and physician global assessment (respectively PGA and PhGA) were rated on a 0–10 numeric scale, every 6 months during 2 years then at 3 years. Only patients with all data available for PGA and PhGA for each of the 6 visits were included. Repeated discordance was defined as an absolute difference |PGA–PhGA|≥3/10 for at least 3 of the 6 visits (i.e., at least half of the visits). Univariable and multivariable logistic models were used to determine if repeated discordance was associated at the 3 years timepoint, with prescription of TNFi, functional incapacity defined as HAQ>0.5, and remission defined as ASDAS-CRP<1.3. Results: Of 401 patients, mean age 34.6±8.7 years, mean symptoms duration 17.8±10.7 months, 219 (54.6%) were female and mean ASDAS-CRP at baseline 2.7±1.0. At 3 years 140 (34.9%) patients had been prescribed a TNFi, 172 (43.2%) had HAQ>0.5 and 89 (25.1%) were in remission. Over the 6 visits, mean PGA was higher than mean PhGA with a mean absolute difference of 0.8±2.2 points. Discordance concerned 110 (27.4%) patients at baseline and repeated discordance concerned 92 (22.9%) patients. In multivariable logistic regression, after adjusting on the others significant factors (which included MRI sacro-iliitis, HLA-B27 and ASDAS-CRP at baseline), repeated discordance was associated with more functional incapacity (61% vs 38%, odds ratio, OR 2.85 [95% CI 1.49–5.62]) and less remission (10% vs 30%, OR 0.38 [0.15–0.85]) but not more TNFi use (34% vs 35%, 1.39 [0.78–2.54] p=0.27). Conclusions: In early axSpA, repeated discordance concerned 22.9% of patients confirming the frequency of this situation. Repeated discordance was associated with worse outcomes at 3 years, even after adjustment of other factors including baseline ASDAS, indicating for the first time that discordance may indeed reflect an unsatisfactory management of medical care leading to worse outcomes. Future studies should concentrate on understanding the reasons of patient-physician discordance for disease activity in axSpA. References: Desthieux C, Molto A, Granger B, Saraux A, Fautrel B, Gossec L. Patient-physician discordance in global assessment in early spondyloarthritis and its change over time: the DESIR cohort. Ann Rheum Dis. 2015 Oct. 22. Dougados M, Etcheto A, Molto A, Alonso S, Bouvet S, Daurès J-P, et al. Clinical presentation of patients suffering from recent onset chronic inflammatory back pain suggestive of spondyloarthritis: The DESIR cohort. Joint Bone Spine. 2015 Oct;82(5):345–51. Acknowledgements: The DESIR cohort is financially supported by unrestricted grants from the French Society of Rheumatology and Pfizer France. These analyses were supported through an unrestricted academic grant from Pfizer France. Disclosure of Interest: None declared